Prediction of dihedral angle regions in tertiary protein structures using neural networks - Soh, Teng Chye. (2009)
In bioinformatics, protein structure prediction is one of the most important goals and research. The three-dimensional structure of proteins is crucial as conformation plays an essential role in the wide ranging biological functions that they perform, hence by predicting and knowing the structure, we will be able to receive information on the function of the protein structure.